Tax Intelligence Analysis in Mitigating the Threat of Tax Evasion Through Transfer Pricing Practices in the Palm Oil Industry: A Case Study of PT Asian Agri Group - Dimas Dwiaryanto; Sundawan Salya; Ivan Yulivan (Security Intelligence Terrorism Journal (SITJ), 2026)
The palm oil sector stands as a strategic pillar for Indonesia's economy, significantly contributing to the nation's GDP and fiscal revenue. However, the industry faces acute non-conventional threats from tax evasion orchestrated via abusive transfer pricing (TP) mechanisms. This study analyzes the root causes and multidimensional impacts of these threats and formulates a robust tax intelligence strategy to safeguard national economic resilience. Adopting a post-positivist paradigm, this qualitative descriptive research evaluates the landmark case of PT Asian Agri Group (AAG), which legally resulted in a state loss of Rp1.25 Trillion. Data collection involved in-depth, semi-structured interviews with eight purposively selected strategic informants across the State Intelligence Agency (BIN), the Directorate General of Taxes (DJP), industry representatives, and tax practitioners. Integrating Creswell’s thematic framework with the Intelligence Analysis Cycle, the findings indicate that the threat level of transfer pricing-driven tax evasion is 'Acute' (Threat Coefficient Score: 19), propelled by a perfect synergy between strategic corporate intent (desire for zero-tax structures) and sophisticated operational capabilities (cross-border shell companies, faked invoicing, and fabricated expenses). Utilizing Barry Buzan’s security matrix, the study shows that the impact spans across economic, political, and societal dimensions, distorting market competition and eroding fiscal sovereignty. Grounded in Arthur F. Lykke Jr.’s strategic model, this paper prescribes a layered intelligence framework emphasizing advanced Big Data Analytics, digital forensically driven evidence gathering to prove mens rea, global data exchange matching (AEoI/CbCR), and interagency enforcement taskforces as a critical deterrence paradigm.